Mental and Emotional Persuasion Tools (the speech of Abullah Ibn Yehia, Head of Ibadyyeh when ruling Yemen) - Basal, Mohammad; Ahmd, Adnan; Fayad , Aksam (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The research presents is an attempt to study the Techniques and tactics of speech which convince the receiver of its notions and ideas so that he takes them for granted then it applies them to a historical text which is "the speech of Abullah Ibn Yehia, Head of Ibadyyeh when ruling Yemen". the research also attempts to make a compromise clarifying both sides of the saying : the theoretical and the practical alongside the tacticse utilized in persuasion. The orator speaker begins with emotional usages emanated from tribal thoughts that both the receiver and the sender embrace taking them from Islamic law principles which evoke fear in the Muslim receiver as they are ready-made arguments. Then they display emotional mental ones that refrain from grabbing the attention of the receiver but make him aware of the disappearance of classes’ differences with the sender. This happens in instructional strategies that enabled him to have an impact upon the receiver knowing his intentions and aim via some data of pragmatic linguistics which rely on argumentation, verbal acts and subtle expressionistic styles deployed in this same context. This pragmatic might be the best when it comes to studying his speech, analyzing it, then unraveling its tools of persuasion taking into account that is a science that studies language in context.